2020
DOI: 10.31315/jik.v17i3.3775
|View full text |Cite
|
Sign up to set email alerts
|

Nilai Budaya dan Gaya Komunikasi Warga Minangkabau, Jawa, dan Bugis

Abstract: Penelitian ini bertujuan menganalisis gaya komunikasi yang berkembang di masyarakat Minangkabau, Jawa, dan Bugis. Penelitian ini menggunakan metode kualitatif teknik pengumpulan data wawancara mendalam (in-depth), pengamatan (obsevasi), dokumentasi, dan literatur. Wawancara dan observasi dilakukan di tiga kota penting: Padang (untuk mencermati gaya komunikasi masyarakat Minangkabau), Surakarta (untuk mencermati gaya komunikasi masyarakat Jawa), dan Makassar (untuk mencermati gaya komunikasi masyarakat Bugis). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
0
1
3
Order By: Relevance
“…However, the findings of this study revealed that in the context of criticism speech acts, Minangkabau people tend to use direct strategies and rarely use reciprocal strategies through rhyme. This tendency contradicts previous studies reported that the cultural values and communication styles of the Minangkabau community, highlighting their inclination towards indirect communication (Pawito et al, 2020) and the use of reciprocation strategies (Arifin, 2020). However, the tendency of this study is supported by Dasrial (2019) who asserts that although the Minangkabau people have a polite language concept or style of communication, known as the concept of Kato nan ampek, its application in daily life is sometimes forgotten or overlooked.…”
Section: 'Off Record' Strategycontrasting
confidence: 99%
“…However, the findings of this study revealed that in the context of criticism speech acts, Minangkabau people tend to use direct strategies and rarely use reciprocal strategies through rhyme. This tendency contradicts previous studies reported that the cultural values and communication styles of the Minangkabau community, highlighting their inclination towards indirect communication (Pawito et al, 2020) and the use of reciprocation strategies (Arifin, 2020). However, the tendency of this study is supported by Dasrial (2019) who asserts that although the Minangkabau people have a polite language concept or style of communication, known as the concept of Kato nan ampek, its application in daily life is sometimes forgotten or overlooked.…”
Section: 'Off Record' Strategycontrasting
confidence: 99%
“…Seperti yang diungkapkan oleh Pawito dkk (2019), perbedaan dalam latar belakang kebudayaan dapat menghasilkan variasi dalam cara berkomunikasi, atau dengan kata lain, identitas budaya memiliki pengaruh terhadap gaya komunikasi individu. (Pawito et al, 2020).…”
Section: Abstrakunclassified
“…Apalagi, setiap orang juga dipengaruhi oleh budaya dan bahasa daerah masing-masing dalam bertutur, seperti anggota dewan di kota Makassar. Hal tersebut berdasarkan penelitian dari Pawito et al (2020) bahwa kebudayaan berpengaruh terhadap gaya komunikasi. Dengan demikian, pola berbicara seseorang tentunya akan berbeda sesuai dengan karakteristik dari budaya daerah masing-masing.…”
Section: Pendahuluanunclassified